Achieving stepwise construction of cyber physical systems in EX-MAN component model - Tauseef Rana; Ayesha Maqbool; Toqir A. Rana; Alina Mirza; Zeshan Iqbal; Muhammad Attique Khan; Majed Alhaisoni; Abdullah Alqahtani; Ye Jin Kim; Byoungchol Chang (Journal of King Saud University: Computer and Information Sciences)
For industry 5.0, constructing new large scale systems by using existing and new technologies is the latest research trend; being a combination of hardware and software technologies, these are referred to as hybrid systems. For constructing large and complex systems, the process of incremental and iterative development is popular for many decades. In the component based software development community, using EX-MAN component model (EX-MAN) a new incremental development process is proposed in this paper. With a new definition on increments, this proposed process is different and beneficial for building systems from existing components in a developer-friendly way. This claim is backed by comparing and contrasting the proposed work with the existing approaches in the component-based development domain. We evaluate our approach by constructing a smart ATM system effective to be used in a pandemic situation. For the support of system construction in EX-MAN, a tool Exogenous Composition Framework is created for modeling and simulation of systems.